2008
DOI: 10.1158/0008-5472.can-08-0488
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Depletion Combined with Anticoagulant Therapy Increases Therapeutic Window of Systemic Treatment with Oncolytic Adenovirus

Abstract: Liver tropism of systemically delivered adenoviruses (Ad)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
94
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 46 publications
5
94
0
Order By: Relevance
“…Emerging evidence highlights the potential of FX in enhancing gene delivery to other cells, including cancer cells, 39,42 epithelial cells, 43 and vascular endothelial cells (C. Nicol and A.H.B., unpublished, January 2009). While the physiologic and/or pathologic role of these interactions remain to be determined, the high-affinity interaction with FX is likely to have broader relevance than effects on liver gene transfer alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence highlights the potential of FX in enhancing gene delivery to other cells, including cancer cells, 39,42 epithelial cells, 43 and vascular endothelial cells (C. Nicol and A.H.B., unpublished, January 2009). While the physiologic and/or pathologic role of these interactions remain to be determined, the high-affinity interaction with FX is likely to have broader relevance than effects on liver gene transfer alone.…”
Section: Discussionmentioning
confidence: 99%
“…We used a low viral dose in this study (10 10 VP/mouse) as the use of clodronate liposomes increases liver transduction approximately 40-fold. 39 It remains unclear as to the involvement of amino acids in the hexon HVRs that are not resolved in the crystal structure in FX binding. From the HVR5 and 7 domain swaps, we can conclude that both regions in their entirety are involved in the high-affinity interaction with FX.…”
mentioning
confidence: 99%
“…The liver tropism of Ad is also responsible for the resultant hepatotoxicity following Ad administration and has raised safety concerns slowing the progression of some vectors to clinical translation. Recent advances in the field have provided several mechanisms to decrease Ad's liver tropism (11), thereby allowing intravascular delivery to be a viable means of administration and decreasing some of the concerns of hepatotoxicity (12). Another limitation has been poor infectivity of target tumor cells by Ad5-based vectors secondary to the decreased expression of the Ad5 primary cellular receptor, the Coxsackie and Adenovirus Receptor (CAR), on target tumor cells.…”
Section: Advanced Generation Crads Circumvent Earlier Obstacles To Efmentioning
confidence: 99%
“…Together, these observations suggested that Ad5-mediated transduction of hepatocytes operate via a CAR-independent pathway. Recently, several studies (7,11,12,16,17,24,26,27) have suggested a fundamental involvement of host proteins, notably coagulation factors, in dictating adenoviral infectivity in vivo. Pivotal to hepatic transduction is the interaction between the Ad5 hexon protein and the coagulation factor X (FX) (7,24,26), which serves to "bridge" the Ad5-FX complex to alternative receptors, which are expressed abundantly within the liver.…”
mentioning
confidence: 99%
“…Pivotal to hepatic transduction is the interaction between the Ad5 hexon protein and the coagulation factor X (FX) (7,24,26), which serves to "bridge" the Ad5-FX complex to alternative receptors, which are expressed abundantly within the liver. Hepatocyte transduction can be abolished by using warfarin (7,12,16,27) to prevent the gamma carboxylation of glutamic acid residues in the N-terminal ␥-carboxyglutamic acid (Gla) domain of FX; the snake venomderived protein X-bp (2), which binds the Gla domain of FX, inhibiting its interaction with hexon (26); or hexon chimeric or mutated Ad5 vectors to abrogate FX binding (7,24,26).…”
mentioning
confidence: 99%